Ahmad Ibrahim dan Sumbangannya dalam Perkembangan Islam di Malaysia: Ahmad Ibrahim and His Contribution in the Development of Islam in Malaysia - Mohammad Hazim Shah, Mohammad Hariz Shah; Buang, Ahmad Hidayat (Journal of Al-Tamaddun, 2021)
Ahmad Ibrahim was one of the key individuals who was responsible in developing the administrative legal system in Malaysia through judicial reform of the Sharia Court. Since colonial period, the Civil Court has been dominating the country’s legal system thus inhibiting the progress and contribution of Islamic law as well as limiting the jurisdiction of the Sharia Court. This article discusses the history of the Islamic law in Malaysia in the judicial administration context as well as analyses the achievement and development of the Sharia Court seen today as a result of the contributions and ideas conceived by Ahmad Ibrahim. This study uses the qualitative method by way of document analysis from books, journal articles, conference papers, newspaper excerpts and statutes such as the Federal Constitution, Acts, Enactments and related cases. The finding suggests that the modern and dynamic landscape of Malaysia Sharia Courts today is the result of Ahmad Ibrahim’s ideas and works through administrative, legal and educational approach which is organic and non-confrontational. This approach is indeed suitable and harmonious in the context of Malaysian multiracial and religious society.